Exploring the Relationship Between Learning Discipline and Emotional Intelligence with Science Learning Outcomes in Fifth-Grade Elementary School Students - Suartini, Luh Wayan Nopa; Suarni, Ni Ketut (Universitas Pendidikan Ganesha, 2024)
The problem faced in science education at the elementary school level is the low academic performance of students, which is often influenced by psychological and behavioral factors. This study aims to analyze the significant simultaneous relationship between learning discipline and emotional intelligence with science learning outcomes in students. This research is of the ex post facto type. Data collection was carried out using test and non-test methods in the form of questionnaires on learning discipline and emotional intelligence as well as science learning outcome test questionnaires. The population of this study consists of 141 students. The sample was determined using total sampling technique. The independent variables in this study are learning discipline and emotional intelligence, while the dependent variable is science learning outcomes. The data were analyzed using descriptive statistics and product-moment correlation analysis. The results show that learning discipline, emotional intelligence, and science learning outcomes are interrelated. There is a significant relationship between learning discipline and science outcomes (Fcount = 0.441 > Ftable = 0.164), emotional intelligence and science outcomes (Fcount = 0.447 > Ftable = 0.164), and between both learning discipline and emotional intelligence with science outcomes (Fcount = 0.250 > Ftable = 0.164). It can be concluded that there is a significant relationship between learning discipline and emotional intelligence on the science learning outcomes of fifth grade elementary school students, both separately and simultaneously. The latest information in this study has implications for improving students' science learning outcomes.